Complete response of merkel cell carcinoma with brain metastases to pembrolizumab and radiotherapy: A case report - Ansgar Koechel; Franz-Joachim Hilke; Bernhard Klumpp; Christopher Schroeder; Thomas Eigentler; Diana Lomberg; Claus Garbe; Ulrike Leiter (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2021)
Merkel cell carcinoma is a rare, but highly malignant and fast growing skin-cancer with high recurrence-rates, deriving from endothelial and neuroendocrine tissues. For advanced Merkel cell carcinoma prognosis is poor [1] and even under cytotoxic chemotherapy there is only a median progression-free survival of only 3 months [2,3]. Even though Merkel cell carcinoma frequently shows lymphatic metastases, it almost never shows cerebral involvement [1]. To our knowledge there are only twelve reported cases of cerebral metastases. Furthermore this is the first reported case of complete response in a patient with advanced Merkel cell carcinoma Stage IV with brain metastases under combined treatment with pembrolizumab and radiotherapy.